Synthesis, NMR spectroscopic characterization and structure of a divinyldisilazane‐(triphenylphosphine)platinum(0) complex: observation of isotope‐induced chemical shifts 1Δ12/13C(195Pt). (11th March 2013) - Wrackmeyer, Bernd; Klimkina, Elena V.; Schmalz, Thomas; Milius, Wolfgang
<x xml:space="preserve">Abstract</x> Tetramethyldivinyldisilazane‐(triphenylphosphine)platinum(0) was prepared, characterized in solid state by X‐ray crystallography and in solution by multinuclear magnetic resonance spectroscopy (1H, 13C, 15N, 29Si, 31P and 195Pt NMR). Numerous signs of spin–spin coupling constants were determined by two‐dimensional heteronuclear shift correlations (HETCOR) and two‐dimensional 1H/1H COSY experiments. Isotope‐induced chemical shifts 1Δ12/13C(195Pt) were measured from 195Pt NMR spectra of the title compound as well as of other Pt(0), Pt(II) and Pt(IV) compounds for comparison. In contrast to other heavy nuclei such as 199Hg or 207Pb, the "normal" shifts of the heavy isotopomers to low frequencies are found, covering a range of >500 ppb. Copyright © 2013 John Wiley & Sons, Ltd.